Role of orthopedia homebox protein in subclassification of pulmonary carcinoid tumors: Retrospective analysis of 110 cases - Mehmet Çetin; Göktürk Fındık; Funda Demirağ; İlteriş Türk; Koray Aydoğdu (Wolters Kluwer Medknow Publications, 2023)
Background: Orthopedia homeobox protein (OTP), highlighted as a sensitive and specific marker for pulmonary carcinoids, may provide a more objective criterion for subclassification. Materials and Methods: A total of 110 patients who underwent surgery for pulmonary carcinoids (2009-2019) were included. Gender, age, application complaint, tumor diameter and location, typical and atypical tumor type, lymph node involvement, stage, recurrence, and survival data were evaluated retrospectively with OTP nuclear staining. Results: The sensitivity of OTP was 66.4%. OTP in subclassifying pulmonary carcinoids was not significant. There was no significant relationship between OTP and lymph node involvement, recurrence, and survival. Conclusion: OTP does not provide significant results in the subclassification of typical and atypical carcinoid tumors and the evaluation of recurrence and survival of carcinoid tumor cases.